Role of Plant Diagnostic Laboratory for identification and management of Insect-pests of Paddy in Kapurthala District - Gurmeet Singh; Manoj Sharma; Jatinder Manan; Gobinder Singh (Journal of Agricultural Extension Management, 2017)
Paddy is grown under different agro-climatic conditions and the crop is damaged by more than 100 species of insect pests and infested by varied diseases. These insect pests cause enormous grain yield losses, which may vary from 20 to 50 per cent if not managed in time. During the last 3 years i.e. from 2013 to 2015, a record of all the visiting farmers was maintained in the plant health diagnostic laboratory at the Krishi Vigyan Kendra, in which complete details of the farmer with address and contact number was maintained. It was noticed that majority of the farmers (80.5%) visited during the month of April and only 19. 5 per cent visited in the month of May as sowing of paddy nursery starts from the first week of May every year. The crop was also found to be prone to micro nutrient deficiency and showed deficiency symptoms in iron and zinc. It was inferred that before the sowing and harvesting of the crop, the farmers queries were maximum due to the fact that majority of insect pest attack takes place near maturity of the crop which results in huge loss, if not taken seriously. As Krishi Vigyan Kendra imparts short duration training to farmers from time to time, it can be concluded that KVK staff should provide training relating to the above mentioned technological problems in a particular month.